Factors Related to The Event of Obesity in The Elderly in Tangerang Selatan - Ade Irma Suryani; Dewi Putri Syarifah; Dinda Hasnatul Salsabila; Dinda Nur Amalia (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
Obesity has reached epidemic proportions globally, with 2.8 million people dying each year as a result of being overweight or obese. Obesity does not only occur in high-income countries, obesity now also occurs in low- and middle-income countries. Some of the factors that cause obesity include lifestyle, diet, and physical activity. Changes in a more modern lifestyle affect the consumption patterns of individuals who tend to consume more fast food which is generally high in fat and sugar, but low in fiber. In addition, individual physical activity tends to decrease due to technological advances. To determine the factors associated with the incidence of obesity in the elderly in South Tangerang. The research methods is qualitative, with a phenomenological approach, purposive sampling, criteria for adequacy, representativeness, willingness, and clarity of informants to explain the objectives of this study. 4 elderly informants residing in South Tangerang, data analysis by triangulation of sources and triangulation of primary and secondary data observation methods. The sub-categories in this study are physical activity, diet, and lifestyle. From the data above, it can be concluded that obesity does not only occur in adolescents and adults, but also in the elderly. Obesity is excess body weight in conditions of abnormal or excessive fat accumulation in adipose tissue. Obesity in the elderly is a health problem because the prevalence of the elderly in the world is increasing. And the causative factors are the lack of physical activity, lifestyle factors, dietary factors.